FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT KEMISKINAN DI PULAU SUMBAWA TAHUN 2004-2009 - , Erwansyah ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The poverty rate in the District / City of Sumbawa Island from year to year tend to fluctuate. Development of varying levels of poverty is not only influenced by the performance and policies of local governments in development but also by all elements of society. Poverty is not something that can not be changed because of public policy and action can help reduce the amount of poverty on the island of Sumbawa. The high level of poverty on the island of Sumbawa in general can be seen from the growing amount of poverty every year. The research was conducted in the District / City of Sumbawa Island by using secondary data with years of observations from the period 2004 to 2009. Research carried out by the approach of literature from various statistical publications with the aim to analyze the effect of GDP growth in the agricultural sector, unemployment, education levels and economic growth on poverty. The data was tested with three methods of pooling data, the method of Ordinary Least Squares (OLS), fixed effect method and the method of random effects. To determine the best method in determining the best model performed Hausman test. Based on the results of Hausman test diproleh best model is the fixed effect method. Based on the analysis with fixed effects methods obtained the following conclusions: a) increased PDRBP not guarantee poverty reduction it is caused by the acquisition of agricultural land is uneven, mostly farmers in rural areas only as tenants only, so do not fully enjoy the fruits of agriculture, b) more high unemployment rates actually reduce poverty, although not significantly. This occurs because most workers become productive workers and families left behind still earn an income, c) education level significantly affects poverty. This can be interpreted that the higher the education level of the opportunity to gain more and more jobs, e) economic growth also has effects on poverty and marked signifkan negative, these results can be interpreted that the higher the economic growth of the income the higher the revenue evenly with the assumption would result in reduced poverty.